Pengembangan The Amazing E-Book Map Materi Kondisi Letak Geografis Peta Indonesia Sebagai Media Belajar Siswa Kelas V SD - Aisyah, Dinda Resa Ayu; Hanifah, Nurdinah; Karlina, Dety Amelia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the difficulties faced by fifth-grade elementary students in understanding the geographical location of Indonesia on a map due to the lack of creative and innovative learning media. Therefore, the study aims to develop a learning media called The Amazing E-Book Map. The research method used is D&D (Design and Development) with the PPE (Planning, Production, and Evaluation) development model. Data was collected through observations, interviews, assessments of media feasibility by subject matter experts and design experts, and user responses (teachers and students). The data analysis employed both qualitative and quantitative descriptive techniques. The results of the media feasibility assessment showed that the subject matter experts gave a score of 88.75%, and the design experts gave a score of 91.42%. The overall average percentage of media feasibility scores from the experts was 90.08%, categorized as